1999
DOI: 10.1093/wber/13.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Do Community-Managed Schools Work? An Evaluation of El Salvador's EDUCO Program

Abstract: This article examines how decentralizing educational responsibility to communities and schools affects student outcomes. It uses the example of El Salvador's Community-Managed Schools Program ^Education con Participation de la Comunidad, EDUCO), which was designed to expand rural education rapidly following El Salvador's civil war. Achievement on standardized tests and attendance are compared for students in EDUCO schools and students in traditional schools. The analysis controls for student characteristics, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
124
0
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 13 publications
2
124
0
11
Order By: Relevance
“…It is easier to regulate and administer large systems uniformly by centralized system but it leads ineffectiveness and costly to address the schools needs differ widely across communities (Jimenez and Sawada, 1998). SBM aims giving schools and communities more autonomous and empowering teachers and parents in decision making or decentralizing educational decision making so that schools reflect priorities and values of local community.…”
Section: School Based Management (Sbm)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is easier to regulate and administer large systems uniformly by centralized system but it leads ineffectiveness and costly to address the schools needs differ widely across communities (Jimenez and Sawada, 1998). SBM aims giving schools and communities more autonomous and empowering teachers and parents in decision making or decentralizing educational decision making so that schools reflect priorities and values of local community.…”
Section: School Based Management (Sbm)mentioning
confidence: 99%
“…The studies show positive effects in attainment. Jimenez and Sawada (1998) found that SBM has been instrumental in involving families and communities in their children are learning in El Salvador. SBM contributes in raising achievement scores and lowering teacher absenteeism.…”
Section: School Based Management (Sbm)mentioning
confidence: 99%
See 1 more Smart Citation
“…To remedy that, decentralised (locally controlled) systems have been implemented in many countries, such as El Salvador and Venezuela. Jimenez and Sawada (1999) analyzed the effectiveness of El Salvador's community-managed (EDUCO) schools. The community participates in hiring and firing teachers, purchasing supplies, and maintenance in EDUCO schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When we split the sample of northern and southern municipalities above and below the median value of the tax evasion indicator in the area, we find that in the North the relationship between 14 See Conning and Kevane (1999), Jimenez and Sawada (1999) and Mookherjee (2001). For instance, large-scale bribery will be more noticeable by local residents who have to pay these bribes and live in close proximity to local government officials (Bardhan and Mookherjee, 2005 (3) and (4) of Table 4).…”
mentioning
confidence: 97%